Understanding Income Taxpayer Behaviour and Professional Zakat Compliance Through a Transcendental Phenomenological Lens - Prasetyo Nugroho Wicaksono, Agung; Iswati, Sri (Universitas Muhammadiyah Surakarta, 2025)
This study aims to find the meaning or interpretation of what has been conveyed by the Income Taxpayer Article 21 and the obligation of professional zakat. The determination of informants was carried out using the purposive sampling method. This study uses an interpretive paradigm with a transcendental phenomenological approach. The units of analysis used in transcendental phenomenology are intentionality, noema, noesis, intuition, and intersubjectivity. The data analysis techniques in this study are through the stages of bracketing, horizonalization, cluster of meaning, textural description, structural description, and composite description (synthesis of meaning and essence). The results of the research obtained four meanings of taxes and zakat that can be inferred from the informant's experience, namely spiritual meaning as a manifestation of obedience to God, physical meaning which is acting because of a rule, mental meaning as a means of forming mental health, and nationalist meaning as a form of strategy against phobias.